Pesquisas sobre a aplicaç\~ao judicial da Lei Maria da Penha: Um levantamento bibliométrico e bibliográfico - Paola Stuker; Tatiana Santos Perrone; Carolina Salazar L'Armée Queiroga de Medeiros Medeiros (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– This is a bibliometric and bibliographic study based on researches about Maria da Penha Law (Law no 11.343/2006) enforcement. It was developed from a literature review for a research project named O Poder Judiciário no enfrentamento à violência doméstica e familiar contra mulheres (CNJ; IPEA, 2019) [The Judiciary facing domestic and familiar violence against women]. Through bibliometrics, which mapped publication dates, knowledge areas, geographic distribution and keywords, we sought to raise the scenario of academic knowledge on Maria da Penha Law published in a decade (2007-2017). More specifically, due to the research project theme, the bibliographic study focused on researches between 2013-2017 about Judiciary law enforcement. Here we show these researches' most common findings and trending discussions, such as different legal practices; debates around punitivism; access to justice and women's autonomy; Judiciary relations with non-criminal networked services to support women in situations of domestic violence. Finally, we present some reflections and concerns according to the results as we appeal to new researches and also point to ranges and prevailing boundaries in the theme.
Keywords: K38; Z18; 330; Maria da Penha Law; Judiciary; violence against women; bibliographic review; bibliometry